2022
DOI: 10.1093/jjco/hyac094
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic value of S-100 protein and Ki-67 index in olfactory neuroblastoma

Abstract: Objective To evaluate the prognostic value of S-100 protein and Ki-67 labeling index in olfactory neuroblastomas. Methods A retrospective study was conducted on a cohort of 85 patients with olfactory neuroblastomas. The immunohistochemical expression of S-100 and Ki-67 was assessed, and the predictive value of S-100 and Ki-67 was further evaluated. The optimal cutoff value of Ki-67 labeling index was determined using time-dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Of the 986 studies found, 11 were included because they satisfied the study's inclusion requirements (between January 2015 and December 2019) [11][12][13][14][15][16][17][18][19][20][21] . In the 11 articles, there were 2284 cases of DLBL.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of the 986 studies found, 11 were included because they satisfied the study's inclusion requirements (between January 2015 and December 2019) [11][12][13][14][15][16][17][18][19][20][21] . In the 11 articles, there were 2284 cases of DLBL.…”
Section: Resultsmentioning
confidence: 99%
“…Variable results were found when the PLR was examined for the prognosis of patients with DLBL. In patients with DLBL, the PLR has been shown to be predictive, though the results have been mixed [11][12][13][14][15][16][17][18][19][20][21] . We found a higher risk of inadequate overall survival and PFS associated with a high PLR based on 11 studies involving 2284 patients with DLBL [11][12][13][14][15][16][17][18][19][20][21] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations